Monolithic SOI pixel detector for x-ray imaging applications with high dynamic range and MHz frame-rate - Peric, I.; Mandl, F. (2011 IEEE Nuclear Science Symposium Conference Record, 2011)
A monolithic pixel detector implemented in 200nm silicon-on-insulator technology for x-ray imaging applications is presented. The photons are detected in the fully-depleted, 500 εm thick, high-resistance substrate. The substrate is isolated by the buried silicon-dioxide from the electronics layer. The pixel electronics is able to measure and digitize photon energy or number of photons in a wide signal range. Typically, for the measurement time of 1 εs, the dynamic range is 10 4 . Thanks to the used ADC structure, the energy response is nearly linear. The detector is a simple and cheap alternative for hybrid pixel x-ray imaging detectors at synchrotron-light- and x-ray free electron laser-sources. Pixel electronics is described and experimental results presented.